Abiotic and biotic factors affecting formation of soil in the Earth - Kafle, Gandhiv (Journal of Agriculture and Natural Resources, 2023)
The soil is formed and affected by a number of biotic and abiotic factors. The soil forming factors are climate, organisms, relief, parent material and time. A review on factors of soil formation was carried out with support from relevant literatures in this study. This review provides an overview of factors of soil formation with relevant research findings which could be useful to undergraduate and graduate students in agriculture and forestry sectors. Climate, organisms, relief, parent material and time are universally accepted factors of soil formation. Recently, ‘human activities’ has been discussed widely for its recognition as a soil forming factor. The soil forming factors are interacting and changing over time, so a system approach may be needed to understand their dynamics and impacts.